Kesenian Kentrung Jepara dalam Perkembangan Zaman - Alamsyah Alamsyah; Siti Maziyah (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2020)
Kentrung art is one of the local arts in Jepara. According to oral tradition, the existence of kentrung around the 16th century. During its development, kentrung reached the peak of popularity in the 20th century. Currently the art of kentrung still survives thanks to the support of the community in performing activities both rituals and entertainment in various places. This condition makes kentrung art still exist in the midst of limited resources of art actors. At the end of the 20th century, along with the development of technology and information, this art was intended to match market needs through more attractive packaging in order to survive. When traditional kentrung retained its old performance style, this art experienced a decline in popularity. From here, kentrung was born, which was modified from the aspects of the equipment, players, and the content of the story to make it more interesting. Even so, kentrung which still maintains its old performance pattern still exists because it has the support of the community, government and cultural community. In order for this art to be sustainable, there needs to be efforts to regenerate actors and innovate performances by still paying attention to traditional values as distinctive and unique local arts